The Financing Higher Education in Malaysia : The Case of Student Loan - Mohd Shawal Ridzuan, Mat Nawi (2011)
In the last few decades, Malaysia has experienced many changes in national higher education system. The government policy towards democratization of education and the positive development in higher education caused the increase in admission of student to public and private higher institutions. Due to this, there exist limitations in term of financial aid to students. In order to reduce the burden of the scholarship system has been replaced with student loans. This research paper attempts to analyses in term of the allocation of resources by the government through PTPTN to students and the relationship between the intakes of students into higher education institutions with total financing provided. In addition, this study also tries to make a comparison between Malaysia and several ASEAN countries in terms of student financing from the aspect of loan provision and methods of loan repayments